Transport and acceleration of the high-current ion beam in magneto-isolated gap - Karas, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2015)
The possibility of transportation and acceleration of the high-current ion beam in the magneto-isolated gap has been demonstrated. Found the parameters of the system and beams (the magnetic field produced by the coils with opposing currents, the size of the system, and the parameters of the beams), under which the uniform acceleration of the high-current ion beam all along the gap length is realized. It is shown that the quality of the ion beam, during transport and acceleration, at the exit of the gap is acceptable for many technological applications. Продемонстровано можливість транспортування та прискорення потужнострумового іонного пучка в магнітоізольованому проміжку. Знайдено параметри системи та пучків (величина магнітного поля, яке створено котушками із зустрічними струмами, розміри системи, параметри пучків), при яких здійснюється рівномірне прискорення по довжині проміжку. Показано, що якість іонного пучка при його транспортуванні та прискоренні на виході з проміжку залишається прийнятною для багатьох технологічних застосувань. Продемонстрирована возможность транспортировки и ускорения сильноточного ионного пучка в магнитоизолированном промежутке. Найдены параметры системы и пучков (величина магнитного поля, созданного катушками со встречными токами, размеры системы, параметры пучков), при которых осуществляется равномерное ускорение по длине промежутка. Показано, что качество ионного пучка при его транспортировке и ускорении на выходе из промежутка остается приемлемым для многих технологических применений.